Metal-doped vanadium oxide with conducting layer and preparation method and application of metal-doped vanadium oxide

By introducing carbon layer and cadmium doping into vanadium oxide and performing in-situ electrochemical activation, a high-performance CdxV2O5-y structure is formed, which solves the problems of slow reaction kinetics and structural stability of vanadium oxides, and realizes the aqueous zinc High capacity and long cycle life of ion batteries.

CN119320169APending Publication Date: 2025-01-17NANJING XIAOZHUANG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411226768.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The slow reaction kinetics of vanadium oxides in zinc-ion batteries, structural collapse and low conductivity lead to capacity attenuation, and existing improvement strategies have failed to fully enhance their electrochemical performance.

Method used

By introducing a carbon layer and cadmium doping into the vanadium oxide and combined with in situ electrochemical activation, a CdxV2O5-y structure rich in oxygen vacancies and water molecules is formed to improve the conductivity and stability of the material.

Benefits of technology

It achieves high capacity, high rate performance and excellent cycle stability, and is simple and safe in process and low energy consumption. It is suitable for the positive electrode material of aqueous zinc ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320169A_ABST
    Figure CN119320169A_ABST
Patent Text Reader

Abstract

The invention discloses a metal-doped vanadium oxide with a conductive layer and a preparation method and application thereof, a carbon layer is used as the conductive layer, the metal-doped vanadium oxide is CdxV2O5-y, x is 0.001-0.01, and y is 0.01-0.5, the preparation method comprises the following steps: (1) mixing a carbon source, a vanadium source and a cadmium source in a solvent, fully stirring and mixing, and drying to obtain a mixed solid; and (2) fully grinding the mixed solid into powder particles, roasting, washing and drying to obtain a product which can be applied to the aqueous zinc ion battery as an electrode material. According to the invention, a simple one-pot thermal reduction and in-situ activation combined method is adopted, structure change is realized through doping and in-situ activation, rich oxygen defects and interlayer water are generated, so that a positive electrode energy band structure is adjusted, and the obtained material shows high capacity, excellent rate capability and good cycle stability, and has good application prospects. And an effective high-performance zinc ion positive electrode preparation scheme is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrodes, and in particular to a metal-doped vanadium oxide with a conductive layer and a preparation method and application thereof. Background Art

[0002] Aqueous zinc-ion batteries are widely used due to their high safety, low cost and high theoretical capacity of zinc anode (820 mAh g -1 ), low reduction potential (0.762V vs. SHE) and excellent ionic conductivity of aqueous electrolytes, it has become a promising alternative. However, the insertion process of zinc ions leads to problems such as slow reaction kinetics and structural collapse due to its large hydration radius and strong interaction with the host lattice. In order to solve these problems, it is critical to find a suitable cathode material with high capacity, fast reaction kinetics and good stability.

[0003] At present, a variety of aqueous zinc-ion battery cathode materials have been studied, including manganese-based compounds, vanadium-based compounds, Prussian blue analogs and conductive polymers. Among them, vanadium-based compounds have become a popular cathode material due to their layered or tunnel structure, low cost and low toxicity. However, the strong electrostatic interaction between zinc ions and vanadium oxides, the low conductivity of the material itself and the structural damage during the cycle process lead to significant capacity decay.

[0004] In order to improve the electrochemical performance of vanadium oxides, researchers have adopted a variety of strategies. The introduction of oxygen vacancies can accelerate the diffusion of zinc ions and improve electronic conductivity; the incorporation of conductive additives such as acetylene black, graphene, and conductive polymers can significantly improve the electronic conductivity of the material. In addition, by inserting cations, polymers, or water molecules into layered vanadium oxides, the ion diffusion capacity can be improved, thereby enhancing the electrochemical reaction kinetics and cycle stability. However, although these improvement strategies have achieved certain results, the overall performance of vanadium oxides has not yet reached the ideal level, and its active site density, structural stability, and electronic / ionic conductivity still need to be further improved. Summary of the invention

[0005] Purpose of the invention: The first purpose of the present invention is to provide a metal-doped vanadium oxide with a conductive layer having high capacity, high rate performance and excellent cycle stability. The second purpose of the present invention is to provide a method for preparing the above-mentioned metal-doped vanadium oxide with a conductive layer. The third purpose of the present invention is to provide an application of the above-mentioned metal-doped vanadium oxide with a conductive layer.

[0006] Technical solution: The metal-doped vanadium oxide with a conductive layer provided by the present invention has a carbon layer as the conductive layer, and the conductive layer is Cd x V2O 5-y, wherein x is 0.001-0.01, y is 0.01-0.5, preferably, x is 0.007-0.03, and more preferably, x is 0.015-0.021; wherein, cadmium will replace part of vanadium atoms with a valence state of +2, be doped into V2O5, and introduce appropriate oxygen vacancies, so that vanadium / oxygen will have multiple valence states at this time, such as vanadium has multiple valence states of +5 / +4 / +3, and oxygen has +5 / +4 valence, and the average valence state is calculated based on the XPS of the material.

[0007] The present invention provides a method for preparing the metal-doped vanadium oxide having a conductive layer, comprising the following steps:

[0008] (1) mixing a carbon source, a vanadium source and a cadmium source in a solvent, stirring and mixing thoroughly, and then drying to obtain a mixed solid;

[0009] (2) The mixed solid is fully ground into powder particles and then calcined. After calcination, it is washed to remove excess ion salts and impurities, and then dried to obtain a metal-doped vanadium oxide with a conductive layer.

[0010] Furthermore, in step (1), the carbon source is glucose, the vanadium source is vanadium pentoxide, the cadmium source is cadmium chloride, and the solvent is hydrogen peroxide solution, with a mass concentration of 1-3 wt.%, preferably 1.5 wt.%.

[0011] Furthermore, in step (1), the molar ratio of the carbon source, the vanadium source and the cadmium source is 0.1-10:1:0.5-3, preferably 1:1:0.5-2.

[0012] Furthermore, in step (1), the drying conditions are: drying at 70-90° C. for 10-24 hours.

[0013] Furthermore, in step (2), the calcination treatment conditions are: placed in a tube furnace, in an inert gas atmosphere, heated to 600-800°C at a heating rate of 5-10°C / min and kept warm for 1-3h; the cleaning reagents are ethanol and deionized water.

[0014] The present invention provides the use of the metal-doped vanadium oxide with a conductive layer as an electrode material in an aqueous zinc ion battery.

[0015] Furthermore, the application method is: metal-doped vanadium oxide with a conductive layer, a conductive agent, and a binder are mixed to form a slurry, which is coated on a current collector, and after vacuum drying, it is used as a positive electrode sheet, and then assembled into an aqueous zinc ion battery in the manner of a positive electrode sheet, a separator, dripping electrolyte, and a negative electrode.

[0016] Furthermore, the mass ratio of the metal-doped vanadium oxide with a conductive layer, the conductive agent, and the binder is 7-8:1-2:1, preferably 7:2:1; the conductive agent is superP or acetylene black; the binder is a polyvinylidene fluoride solution with a mass concentration of 20 to 30 mg / mL; the current collector is a stainless steel mesh or titanium foil; the electrolyte is a zinc trifluoromethanesulfonate electrolyte with a molar concentration of 2-3 mol / L; and the negative electrode is a zinc sheet.

[0017] Furthermore, the method further comprises in-situ activation: charging the aqueous zinc ion battery to a voltage of 1.8V for the first cycle to in-situ activate the metal-doped vanadium oxide having a conductive layer, thereby obtaining a metal-doped vanadium oxide positive electrode material having a conductive layer rich in oxygen vacancies and water molecules, denoted as Cd x1 V2O 5-y1 ·nH2O@C, wherein x1 is 0.003-0.01, y1 is 0.09-0.3, and x1<x. This is because when the amount of cadmium salt added is different, different doping amounts of cadmium and oxygen vacancies exist in the material, so x1 is variable. Different raw material proportions lead to changes in sample parameters. The in-situ activation current is 0.05-0.3A / g.

[0018] Principle of the invention: In the present invention, the performance of vanadium oxide is improved by a structural modification strategy of carbon layer coating and cadmium doping combined with in-situ electrochemical activation; the electronegativity of cadmium atoms (1.69) is higher than that of vanadium (1.63), which enhances the CdVO x The cadmium-oxygen bond energy in the @C structure improves the stability of the oxide lattice and reduces its dissolution during the electrochemical cycle, thereby improving the cycle stability of the positive electrode material during the cycle.

[0019] The electrode material prepared by the method of the present invention is converted into a positive electrode material rich in oxygen vacancies and water molecules after in-situ electrochemical activation, showing high capacity, high rate performance and excellent cycle stability.

[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The one-pot hot solid-state reduction technology used can facilitate the mass production of electrode materials; (2) Based on the electrochemical principle, the vanadium trioxide positive electrode charged to 1.8V will irreversibly transform into a vanadium pentoxide material. This process does not require any other steps. The battery can be activated in situ after preparation. The method is simple, the activation time is short, and the energy consumption is low; (3) The prepared aqueous zinc ion battery positive electrode material has excellent performance: high capacity, at 0.2Ag -1 At a current density of 420 mAh g -1 Specific capacity; excellent rate performance, at 20Ag -1 At this current density, there is still 198 mAh g -1High specific capacity; long cycle life, at 20Ag -1 After 3500 cycles at the current density, it has an excellent capacity retention rate of 78.5%; (4) The present invention does not involve dangerous chemical reagents and special chemical reaction equipment, and the entire process is simple and safe to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a scanning electron microscope image of the electrode material prepared in Example 1;

[0022] Figure 2 The rate performance diagram of the electrode materials with different cadmium doping amounts prepared in Example 1;

[0023] Figure 3 This is a cycle performance diagram of the electrode material prepared in Example 1;

[0024] Figure 4 The figure is a rate performance diagram of the electrode materials prepared in Example 1 and Comparative Examples 1 to 6;

[0025] Figure 5 The cycle performance diagram of the electrode material prepared in Example 2 at different folding angles;

[0026] Figure 6 This is a picture of the electrode material prepared in Example 2 lighting up an LED lamp at different folding angles. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with specific embodiments and drawings.

[0028] Example 1: The metal-doped vanadium oxide electrode material with a conductive layer provided in this example has a carbon layer as the conductive layer, and the metal-doped vanadium oxide is Cd x V2O 5-y , where x is 0.007-0.03 and y is 2.07-2.13.

[0029] The preparation method of the metal-doped vanadium oxide electrode material with a conductive layer is as follows: glucose monohydrate, vanadium pentoxide, and cadmium chloride are weighed and dissolved in a 1.5wt.% hydrogen peroxide solution according to a molar ratio of 1:1:z (z is 0.5, 1, 1.5, and 2, respectively), and the mixture is placed in a blast drying oven after continuous stirring for 24 hours, and dried at 80°C in an air atmosphere for 12 hours until the mixture is completely dry. Then the mixture is transferred to a mortar and ground into powder particles, which are then placed in a tube furnace and heated to 700°C at a heating rate of 5°C / min in an argon atmosphere and kept warm for 1 hour. The calcined sample is then washed three times with ethanol and deionized water to remove excess cadmium salts and impurities, and the black powder obtained after drying again is the electrode material. According to the different amounts of cadmium salt added, the following are obtained from the amount of cadmium salt added from low to high: Cd0.007 V2O 2.93 , Cd 0.015 V2O 2.92 , Cd 0.021 V2O 2.91 , Cd 0.03 V2O 2.87 When the ratio of glucose monohydrate, vanadium pentoxide and cadmium chloride is 1:1:1, the obtained Cd 0.015 V2O 2.92 Electron microscope images of electrode materials are shown below: Figure 1 As shown in the figure, it can be seen that the electrode material is agglomerated with round particles, and the size is about 30 to 40 nm.

[0030] The metal-doped vanadium oxide having a conductive layer is used as an electrode material in an aqueous zinc ion battery, and the method is as follows:

[0031] (1) When the raw materials of glucose monohydrate, vanadium pentoxide and cadmium chloride are in a ratio of 1:1:1, the obtained Cd 0.015 V2O 2.92 As an example of electrode material, Cd 0.015 V2O 2.92 As the active substance, weigh Cd 0.015 V2O 2.92 14g, superP4g, 20mg / LPVDF solution 100mL were stirred for 12h to prepare slurry; the slurry was coated on a 0.05mm titanium foil with a 120mm scraper, then transferred to a vacuum drying oven and dried at 80℃ for 12h to obtain a loading of 1.0g / cm 2 Positive electrode.

[0032] (2) The positive electrode sheet in step (1) was cut into a circular button cell positive electrode with a diameter of 12 mm, 3 mol / L zinc trifluoromethanesulfonate was used as the electrolyte, a 0.1 mm zinc sheet was used as the negative electrode, and a glass fiber membrane was used as the separator to prepare a CR2032 button type zinc ion battery.

[0033] The prepared button battery can be directly activated and electrochemically tested on a CT-4008T-164. The Cd 0.004 V2O 4.85 nH2O@C positive electrode material. According to this method, the positive electrode obtained when the ratio of glucose monohydrate, vanadium pentoxide, and cadmium chloride is 1:1:0.5 / 1.5 / 2 is Cd 0.003 V2O 4.82 ·nH2O@C,Cd 0.007 V2O 4.7 ·nH2O@C,Cd0.01 V2O 4.91 ·nH2O@C.

[0034] Figure 2 The button cells made of the positive electrode materials prepared by adding different contents of cadmium chloride in Example 1 have rate performance at different currents, and the charge and discharge range is 0.2-1.8V. 0.004 V2O 4.85 ·nH2O@C at 0.2Ag -1 At a current density of 420 mAh g -1 Specific capacity; at 20Ag -1 At this current density, there is still 198 mAh g -1 Specific capacity.

[0035] Figure 3 The Cd prepared in Example 1 0.004 V2O 4.85 ·Button cell with nH2O@C as cathode material, at 20Ag -1 The cycling performance under current density shows that the capacity retention rate is still 78.5% after 3500 cycles.

[0036] Comparative Example 1: The electrode material provided in this comparative example is V2O 4.93 @C.

[0037] The preparation method is the same as that of Example 1, except that cadmium chloride is removed.

[0038] The application method is the same as in Example 1, and the prepared positive electrode material is V2O 4.93 ·nH2O@C.

[0039] Comparative Example 2: The electrode material provided in this comparative example is Ru 0.014 V2O 2.93 @C.

[0040] The preparation method is the same as that of Example 1, except that ruthenium chloride is substituted for cadmium chloride.

[0041] The application method is the same as in Example 1, and the prepared positive electrode material is Ru 0.005 V2O 4.95 ·nH2O@C.

[0042] Comparative Example 3: The electrode material provided in this comparative example is Rb 0.014 V2O 2.91 @C.

[0043] The preparation method is the same as that of Example 1, except that rubidium chloride is used instead of cadmium chloride.

[0044] The application method is the same as in Example 1, and the positive electrode material prepared is Rb0.005 V2O 4.91 ·nH2O@C.

[0045] Comparative Example 4: The electrode material provided in this comparative example is Ti 0.016 V2O 2.91 @C.

[0046] The preparation method is the same as that of Example 1, except that titanium tetrachloride is used instead of cadmium chloride.

[0047] The application method is the same as in Example 1, and the prepared positive electrode material is Ti 0.006 V2O 4.94 ·nH2O@C.

[0048] Comparative Example 5: The electrode material provided in this comparative example is Cu 0.014 V2O 2.93 @C.

[0049] The preparation method is the same as that of Example 1, except that cupric chloride is used instead of cadmium chloride.

[0050] The application method is the same as in Example 1, and the prepared positive electrode material is Cu 0.006 V2O 4.93 ·nH2O@C.

[0051] Comparative Example 6: The electrode material provided in this comparative example is Fe 0.017 V2O 2.93 @C.

[0052] The preparation method is the same as that of Example 1, except that ferric chloride is used instead of cadmium chloride.

[0053] The application method is the same as in Example 1, and the prepared positive electrode material is Fe 0.004 V2O 4.87 ·nH2O@C.

[0054] The Cd prepared in Example 1 0.004 V2O 4.85 The test results of the materials prepared by nH2O@C and Comparative Examples 1 to 6 are shown in Figure 4 .Depend on Figure 4 It can be seen that the rate performance at different currents is in the range of 0.2-1.8V. The best one is the Cd prepared in Example 1. 0.004 V2O 4.85 ·nH2O@C at 0.2Ag -1 At a current density of 420 mAh g -1 Specific capacity; at 20Ag -1 At this current density, there is still 198 mAh g -1Compared with the optimal cadmium-doped sample, the Ru generated by doping with other chloride salts (ruthenium chloride / rubidium chloride / titanium tetrachloride / copper chloride / ferric chloride) 0.005 V2O 4.95 ·nH2O@C,Rb 0.005 V2O 4.91 ·nH2O@C,Ti 0.006 V2O 4.94 nH2O@C,Cu 0.006 V2O 4.93 nH2O@C,Fe 0.004 V2O 4.87 nH2O@C positive electrode at 0.2Ag -1 At the current density, they have an average of 312 mAh g -1 , 400mAh g -1 , 158mAh g -1 , 225mAh g -1 , 248mAh g -1 Specific capacity, both in capacity and rate performance are inferior to Cd 0.004 V2O 4.85 ·nH2O@C. This is because compared with the doping of other different ions, the introduction of cadmium has the most suitable structure during the electrochemical activation process, which can effectively reduce the energy barrier of zinc migration and the structural deformation produced during the cycle process, thus having excellent zinc ion battery positive electrode performance.

[0055] Example 2: The metal-doped vanadium oxide with a conductive layer provided in this example has a carbon layer as the conductive layer, and the metal-doped vanadium oxide is Cd 0.027 V2O 2.91 .

[0056] The preparation method of the metal-doped vanadium oxide electrode material with a conductive layer is as follows: glucose monohydrate, vanadium pentoxide, and cadmium chloride are weighed in a molar ratio of 1:1:1.6 and dissolved in a 1.5wt.% hydrogen peroxide solution. After continuous stirring for 24 hours, the beaker is placed in a forced air drying oven and dried at 80°C in an air atmosphere for 12 hours until the mixture is completely dry. It is then transferred to a mortar and ground into powder particles, which are then placed in a tubular furnace and heated to 700°C at a heating rate of 5°C / min in an argon atmosphere and kept warm for 1 hour. The calcined sample is taken out and washed three times with ethanol and deionized water to remove excess metal salts and impurities. The black powder obtained after drying again is the electrode material Cd 0.027 V2O 2.91 @C.

[0057] The application of the metal-doped vanadium oxide electrode material having a conductive layer in an aqueous zinc ion battery is as follows:

[0058] (1)Cd 0.027 V2O 2.91 @C is used as the active substance, and Cd 0.027 V2O 2.91 @C14 g, super P 4 g, 20 mg / LPVDF solution 100 mL was stirred for 12 h to prepare a slurry; the slurry was coated on a 0.05 mm titanium foil with a 500 mm scraper, then transferred to a vacuum drying oven and dried at 80 ° C for 12 h to obtain a loading of 4.0 g / cm 2 Positive electrode;

[0059] (2) The positive electrode sheet in step (1) was cut into rectangular battery positive electrode sheets with a length and width of 3*2 cm respectively, 3 mol / L zinc trifluoromethanesulfonate was selected as the electrolyte, 0.1 mm zinc sheet was used as the negative electrode, and glass fiber membrane was used as the separator to prepare a soft-pack zinc ion battery.

[0060] The prepared soft-pack zinc-ion battery can be directly activated and electrochemically tested on the Xinwei (CT-4008T-164) in situ. The Cd 0.008 V2O 4.87 nH2O@C cathode material.

[0061] Figure 5 The Cd prepared in Example 2 0.008 V2O 4.87 @C is the cycling performance of the soft-pack battery with positive electrode material under different bending conditions. -1 The current density is charged and discharged, and after 20 cycles, there is still 299mAh g -1 Specific capacitance.

[0062] Figure 6 The Cd prepared in Example 2 0.008 V2O 4.87 ·Practicality test of soft-pack batteries with nH2O@C as positive electrode material under different bending conditions. It can be seen that under different bending conditions of 0°, 45°, 90°, and 180°, the prepared soft-pack batteries can effectively light up LED lamps.

Claims

1. A metal-doped vanadium oxide having a conductive layer, characterized in that: The carbon layer is used as the conductive layer, and the metal doped vanadium oxide is Cd x V2O 5-y , where x is 0.001-0.05 and y is 0.01-0.

5.

2. The metal-doped vanadium oxide having a conductive layer according to claim 1, characterized in that: The x is 0.007-0.

03.

3. A method for preparing the metal-doped vanadium oxide having a conductive layer according to claim 1, characterized in that: The following steps are involved: (1) mixing a carbon source, a vanadium source and a cadmium source in a solvent, stirring and mixing thoroughly, and then drying to obtain a mixed solid; (2) The mixed solid is fully ground into powder particles and then calcined. After calcination, it is washed to remove excess ion salts and impurities, and then dried to obtain a metal-doped vanadium oxide with a conductive layer.

4. The preparation method according to claim 3, characterized in that: In step (1), the carbon source is glucose, the vanadium source is vanadium pentoxide, the cadmium source is cadmium chloride, and the solvent is hydrogen peroxide solution with a mass concentration of 1-3wt.%; the molar ratio of the carbon source, the vanadium source and the cadmium source is 0.1-10:1:0.5-2.

5. The preparation method according to claim 3, characterized in that: In step (1), the drying conditions are: drying at 70-90° C. for 10-24 hours.

6. The preparation method according to claim 3, characterized in that: In step (2), the calcination treatment conditions are: placing in a tubular furnace, in an inert gas atmosphere, heating to 600-800° C. at a heating rate of 5-10° C. / min and keeping warm for 1-3 hours.

7. Use of the metal-doped vanadium oxide with a conductive layer as claimed in claim 1 as an electrode material in an aqueous zinc ion battery.

8. The use according to claim 7, characterized in that: The method is as follows: metal-doped vanadium oxide with a conductive layer as an electrode material, a conductive agent, and a binder are mixed to form a slurry, which is coated on a current collector and vacuum dried as a positive electrode sheet. The aqueous zinc ion battery is then assembled in the manner of a positive electrode sheet, a separator, an electrolyte solution, and a negative electrode.

9. The use according to claim 8, characterized in that: The mass ratio of the metal-doped vanadium oxide with a conductive layer, the conductive agent, and the binder is 7-8:1-2:1; the conductive agent is superP or acetylene black; the binder is a polyvinylidene fluoride solution with a mass concentration of 20-30 mg / mL; the current collector is a stainless steel mesh or titanium foil; the electrolyte is a zinc trifluoromethanesulfonate electrolyte with a molar concentration of 2-3 mol / L; and the negative electrode is a zinc sheet.

10. The use according to claim 8, characterized in that: The method further comprises in-situ activation: charging the aqueous zinc ion battery to a voltage of 1.8V for the first cycle to in-situ activate the metal-doped vanadium oxide with a conductive layer, thereby obtaining a metal-doped vanadium oxide positive electrode material Cd with a conductive layer rich in oxygen vacancies and water molecules. x1 V2O 5-y1 ·nH2O@C, wherein x1 is 0.003-0.01, y1 is 0.09-0.3; and the current of the in-situ activation is 0.05-0.3 A / g.

Citation Information

Cited By

  • Vanadium-based alloy compound composite material as well as preparation method and application thereof

    CN119965245A